Discrimination capacity of the pirate test to detect vision disorders in preschool children - Ku Lozano, Jenny Kam Lin; Osada, Jorge Enrique; Ku Lu, Eduardo Maron; Lozano Ponce, Maria Esther; Samudio, Margarita (Medicina Clínica y Social, 2025)
Introduction: The presence of amblyopia due to untreated vision disorders is a serious global problem, which prevalence will increase from 13 to 26% in 2060. Despite having stablished screening programs for early detection of vision disorders in schools and training teachers for the correct use of ophthalmic instruments. However, due to the high rate of false positive results, its validity decreased. This situation implies the need to find a simple, low cost and reproducible test that allows the detection of vision disorders without prior ophthalmological knowledge, which is the main reason why the Pirate Test was proposed. Objective: To determine the discrimination capacity of Pirate Test to detect vision disorders in preschool children in Piura city. Methodology: Diagnostic study test (“Pirate Test”) was applied to 447 preschoolers by their parents and then they were evaluated by an ophthalmologist who determined if they really had vision disorders and specify the validity of the applied Test through the analysis of its sensitivity (Se), specificity (Sp), and ROC curve using SPSS v16. Results: The Se and Sp values to detect refractive errors were 85.4% and 78.8%, whereas for amblyopia the values were 83% and 93.7%, respectively. Also, ROC curves in both cases reported good discrimination capacity to detect visual disorders and amblyopia. Conclusion: Pirate Test has good discrimination capacity to detect visual disorders and amblyopia in preschoolers. The cut-off point was less than 5 minutes, which implies that the possibility of having important visual disorders or amblyopia is high.
Keywords: Tamizaje; trastornos de la visión; ambliopía; preescolar